European takeover law: the case for a neutral approach - Luca Enriques (Fondazione Eni Enrico Mattei (FEEM), 2010)
This paper argues that in revising the Takeover Bid Directive, EU policymakers should adopt a neutral approach toward takeovers, i.e. enact rules that neither hamper nor promote them. The rationale behind this approach is that takeovers can be both value-creating and value-decreasing and there is no way to tell ex ante whether they are of the former or the latter kind. Unfortunately, takeover rules cannot be crafted so as to hinder all the bad takeovers while at the same time promoting the good ones. Further, contestability of control is not cost-free, because it has a negative impact on managers' and block-holders' incentives to make firm-specific investments of human capital, which in turn affects firm value. It is thus argued that individual companies should be able to decide how contestable their control should be. After showing that the current EC legal framework for takeovers overall hinders takeover activity in the EU, the paper identifies three rationales for a takeover-neutral intervention of the EC in the area of takeover regulation (pre-emption of 'takeover-hostile,' protectionist national regulations, opt-out rules protecting shareholders vis-à-vis managers' and dominant shareholders' opportunism in takeover contexts, and menu rules helping individual companies define their degree of control contestability) and provides examples of rules that may respond to such rationales.
Keywords: K22; G34; G38; 330; Takeover Bid Directive; Board Neutrality; Mandatory Bid Rule; Market for Corporate Control